+0  
 
0
54
1
avatar

There exist constants a, h, and k such that

3x^2 + 12x + 4 - 2x^2 + 11x - 7 = a(x - h)^2 + k

for all real numbers Enter the ordered triple (a,h,k).

 Feb 3, 2021
 #1
avatar+425 
0


3x^2 + 12x + 4 - 2x^2 + 11x - 7 = a(x - h)^2 + k

x^2 + 23x - 3 = a(x - h)^2 + k (Combining like terms)

(x+11.5)^2 = x^2 + 23x + 132.5 (factor)

 

(x+11.5)^2 - 135.5 = a(x - h)^2 + k (replacing)

 

And we have our answer :)))

(1, 11.5, -135.5)

 

I hope this helped

 

=^._.^=

 Feb 3, 2021

83 Online Users

avatar
avatar
avatar